2005
DOI: 10.1124/jpet.105.087890
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of l-Carnitine and Its Short-Chain Ester Propionyl-l-carnitine in the Isolated Perfused Rat Liver

Abstract: Hepatic uptake of propionyl-L-carnitine (PLC) and L-carnitine (LC) was assessed with the impulse-response technique in the single-pass perfused rat liver. The experiments involved a rapid injection (impulse) of a mixture of the radiolabeled test compound (PLC or LC) and a reference compound (sucrose) into portal vein inflow and collection and radiochemical analysis (response) of the venous outflowing perfusate samples. The impulse injection was made in the presence of increasing unlabeled background concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…6), in which CP caused necrosis and inflammation in both glomeruli and renal tubules. Since more than 90% of filtered carnitine is reabsorbed at the proximal tubules [16], tubular damage induced by CP [10,32] may lead to inhibition of endogenous carnitine biosynthesis and increase its clearance, with consequent secondary deficiency of the molecule. Moreover, CP might inhibit the action of sodium-dependent organic cation/carnitine transporter (OCTN2) with consequent decrease in carnitine reabsorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6), in which CP caused necrosis and inflammation in both glomeruli and renal tubules. Since more than 90% of filtered carnitine is reabsorbed at the proximal tubules [16], tubular damage induced by CP [10,32] may lead to inhibition of endogenous carnitine biosynthesis and increase its clearance, with consequent secondary deficiency of the molecule. Moreover, CP might inhibit the action of sodium-dependent organic cation/carnitine transporter (OCTN2) with consequent decrease in carnitine reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…L-Carnitine is an essential cofactor for translocation of long-chain fatty acids from cytoplasmic compartment into mitochondria, where beta-oxidation enzymes are located, for energy production [15]. It is well known that L-carnitine is highly conserved, since more than 90% of filtered carnitine is reabsorbed at the proximal tubular level [16]. Although the kidney is the main organ responsible for endogenous synthesis of L-carnitine, we could not find any study in the literature to date investigating the effects of CP on kidney function under condition of carnitine depletion and supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, although it was suggested that acetylcarnitine is partly hydrolyzed in enterocytes, oral doses of acetylcarnitine increased the corresponding plasma concentrations by 40% (Rebouche, 2004). The bioavailability of propionylcarnitine has not been determined specifically in mice, but has been estimated to be less than 20% (Mancinelli et al, 2005). Our study was not designed as a pharmacokinetic study, but nevertheless allowed to estimate some kinetic parameters of the administered compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Also, competition may occur between PLC, L -carnitine and acetylcarnitine for the tubular reabsorption transport systems [51] . Moreover, renal metabolism of PLC to L -carnitine and acetylcarnitine, followed by migration of the locally formed metabolites directly to the urine, could also be involved [52] . In reality, all three mechanisms (saturation, competition and renal metabolism) are likely to be contributing to the observed increase in renal excretion of carnitine after PLC administration [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%